Diet of Adult Sardine Sardina pilchardus in the Gulf of Trieste, Northern Adriatic Sea - Diego Borme; Sara Legovini; Alessandra de Olazabal; Valentina Tirelli (Journal of Marine Science and Engineering, 2022)
Food availability is thought to exert a bottom-up control on the population dynamics of small pelagic fish; therefore, studies on trophic ecology are essential to improve their management. Sardina pilchardus is one of the most important commercial species in the Adriatic Sea, yet there is little information on its diet in this area. Adult sardines were caught in the Gulf of Trieste (northern Adriatic) from spring 2006 to winter 2007. Experimental catches conducted over 24-h cycles in May, June and July showed that the sardines foraged mainly in the late afternoon. A total of 96 adult sardines were analysed: the number of prey varied from a minimum of 305 to a maximum of 3318 prey/stomach, with an overall mean of 1259 ± 884 prey/stomach. Prey items were identified to the lowest possible taxonomical level, counted and measured at the stereo-microscope. Overall, sardines fed on a wide range of planktonic organisms (87 prey items from 17 μm to 18.4 mm were identified), with copepods being the most abundant prey (56%) and phytoplankton never exceeding 10% of the prey. Copepods of the Clauso-Paracalanidae group and of the genus Oncaea were by far the most important prey. The carbon content of prey items was indirectly estimated from prey dry mass or body volume. Almost all carbon uptake relied on a few groups of zooplankton. Ivlev’s selectivity index showed that sardines positively selected small preys (small copepods < 1 mm size), but also larger preys (such as teleost eggs, decapod larvae and chaetognaths), confirming their adaptive feeding capacity.